DLPFC stimulation alters large-scale brain networks connectivity during a drug cue reactivity task: A tDCS-fMRI study - Soleimani, Ghazaleh; Towhidkhah, Farzad; Oghabian, Mohammad Ali; Ekhtiari, Hamed (Frontiers in Systems Neuroscience, 2022)
Transcranial direct current stimulation (tDCS) is a promising intervention for reducing craving/consumption in individuals with substance use disorders. However, its exact mechanism of action has not yet been well explored. We aimed to examine the network-based effects of tDCS while people with methamphetamine use disorders (MUDs) are exposed to drug cues. In a randomized double-blind sham-controlled trial with a crossover design, fifteen participants with MUDs were recruited to receive 20 minutes of active/sham tDCS with anode/cathode over F4/F3. MRI data including structural and task-based functional MRI during a standard drug cue-reactivity task were collected immediately before and after stimulation sessions. Craving scores were also recorded before and after MRI scans. Individualized head models were generated to determine brain regions with strong electric fields (EFs). Using atlas-based parcellation of head models, averaged EFs were extracted from main nodes of three large-scale networks that showed abnormalities in MUDs; executive control (ECN), default mode (DMN), and ventral attention (VAN) networks. Main nodes with strong EF intensity were used as seed regions for task-based functional connectivity (using generalized psychophysiological interaction (gPPI)) and activity (using a general linear model (GLM)) calculations. Subjective craving showed a significant reduction in immediate craving after active (-15.42±5.42) compared to sham (-1±2.63). In seed-to-whole brain results, the PFC node in ECN showed an enhanced PPI connectivity with precuneus and visual cortex; the cluster center in MNI (6, -84, -12), PFC node in DMN showed a decreased PPI connectivity with contralateral parietal cortex;(-48, -60, 46). ROI-to-ROI results showed increased PPI connectivity within/between ECN-VAN while connectivity between ECN-DMN was decreased. In line with connectivity, functional activity in right PFC node in DMN decreased after tDCS while activity in PFC nodes of ECN/VAN was increased. EF calculations in PFC nodes revealed that EF in DMN was outward while the direction of EFs was inward in ECN/VAN. Current study provides new insight into neural circuitry underlying MUDs that can be modulated by tDCS at network-level and specifically suggest that bilateral tDCS increases cortical excitability in ECN and VAN while it has opposite effects on DMN that may be related to the direction of EFs.